Analisis Model Evaluasi CIPP dalam Pengelolaan Dana Desa di Desa Bahitom Kecamatan Murung Kabupaten Murung Raya - Habibi Habibi; Taufik Arbain (MAN 4 Kota Pekanbaru, 2026)
This research is motivated by the ongoing issue of unaccountable Village Fund management, despite Bahitom Village being designated as an Anti-Corruption Pilot Village. This study aims to evaluate Village Fund management in Bahitom Village, Murung District, Murung Raya Regency, based on the CIPP (Context, Input, Process, Product) Evaluation Model, and identify supporting and inhibiting factors. The research employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing. The results indicate that Village Fund management planning is based on community needs through Village Deliberations, thus aligning with development conditions and priorities (context). Village Fund implementation is realized through infrastructure development, improved village government services, and community empowerment, providing tangible benefits (product). Administration is supported by budget availability, organizational structure, and the use of the Village Finance System (Siskeudes) application, which reflects resource availability (input). Reporting and accountability have been carried out in accordance with procedures, applying the principles of transparency, participation, and accountability (process). Supporting factors include cooperation between the village government and the community, community participation, and regulatory support. Inhibiting factors include budget limitations, human resource limitations, and delays in submitting reporting information.